1984
DOI: 10.1021/bi00300a023
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR relaxation studies of the hydrogen-bonded imino protons of poly(dA-dT)

Abstract: Measurements on the thymine imino proton relaxation rates have been used to study various structural and dynamic properties of 53 +/- 15 base pair long poly(dA-dT). Below 10 degrees C, the relaxation is dominated by dipolar magnetic interactions. At 1 degrees C the relaxation of the transverse magnetization is exponential (R2 = 124 s-1), but the relaxation of longitudinal magnetization is highly nonexponential due to spin-diffusion effects (initial decay rate constant of 28 s-1 and a slower rate of approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

1985
1985
1990
1990

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 53 publications
2
39
1
Order By: Relevance
“…'~ Zn ( I1 ) is required for the function of many regulatory proteins. As the protein binds to dA-dT rich regions, the water activity around the DNA will be lowered and the presence of the Zn (11) near these regions may induce the C structure. Even though the C structure is only slightly overwound with respect to the B structure, this small change could maximize the protein-DNA interactions required to produce the specific binding.…”
Section: Discussionmentioning
confidence: 99%
“…'~ Zn ( I1 ) is required for the function of many regulatory proteins. As the protein binds to dA-dT rich regions, the water activity around the DNA will be lowered and the presence of the Zn (11) near these regions may induce the C structure. Even though the C structure is only slightly overwound with respect to the B structure, this small change could maximize the protein-DNA interactions required to produce the specific binding.…”
Section: Discussionmentioning
confidence: 99%
“…Poly[d(G-C)] (P-L Biochemicals, lot 676-7) was sonicated to =60 base pairs (14,15), precipitated with ethanol, dissolved in 0.125 ml of buffer containing 4.5 M NaCl (or 3.25 M Na-C104) and 0.01 M sodium cacodylate at pH 7, and placed in a Wilmad 508-CP NMR microcell. Real-time solvent-exchange experiments were performed by first equilibrating the Z-DNA in buffer containing 'H20.…”
Section: Methodsmentioning
confidence: 99%
“…We have been studying the exchange of the imino protons in short (-60-base-pair) DNA polymers by NMR relaxation techniques (13)(14)(15)), but we found that exchange from Z-form poly[d(G-C)] was too slow (<1 s-1 at 850C) to use this approach. Nevertheless, using our data to estimate the exchange rate at high temperature and the Ramstein and Leng (10) rate obtained at low temperature, we calculated an apparent exchange activation energy of only 12 kcal/mol (1 kcal = 4.18 kJ).…”
mentioning
confidence: 99%
“…A good tit is obtained with a model featuring torsional motions (0.1 -1.5 ns, f 30" amplitude) in addition to out of plane motions (1 -100 ns, f30" amplitude). The combination of these two motions can also be simulated by a 'jumping on a cone' model (1 ns, $30" amplitude) [110]. In-plane and out-of-plane motions of the bases, with amplitudes of about lo", are also implied by 2H relaxation data of G(2H8) [8-'H]G-deuterated calf thymus DNA in the, oriented, hydrated, solid state [118].…”
Section: Intru-molecular Mobilitymentioning
confidence: 99%